Pengaruh Model Kooperatif Tipe Scramble Berbantuan Media Flashcard Terhadap Keterampilan Membaca Permulaan Peserta Didik di Sekolah Dasar - Sarmiyati Sarmiyati; Arifin Ahmad; Feby Inggriyani (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to address the low initial reading ability of second-grade students who have not yet met the Minimum Mastery Completion Criteria (KKTP) due to the use of conventional learning methods. This study analyzes the differences in initial reading ability between students who learn using the cooperative learning model of scramble type integrated with flashcard media and students who learn with conventional learning, and measures the magnitude of the effect of the treatment. The study used a quantitative approach with a quasi-experimental method through a non-equivalent control group design. The research sample consisted of 48 second-grade students of SDN Cinangka 1 Bandung, divided into an experimental class (24 students) and a control class (24 students). Data were collected through pre-tests and post-tests, then analyzed using the Mann–Whitney U test and the Rank-Biserial Correlation effect size with the help of JASP software. The results of the analysis showed no significant difference in the initial abilities of the two groups (p = 0.386). After treatment, there was a very significant difference in the initial reading learning outcomes (p < 0.001), with the average post-test score of the experimental class being higher than that of the control class. The effect size was in the large category. The results of the study showed that the application of the flashcard-assisted scramble model was effective in improving students' initial reading skills.